Impact of recycled manure solids bedding on hygiene and odds of hock lesions in dairy cows - Fréchette, Annie; Fecteau, Gilles; Dufour, Simon (Frontiers in Veterinary Science, 2022)
The use of RMS as bedding for dairy cows has become more popular over the last decade. Once producers own the RMS producing equipment, they are not restricted in the amount of bedding they can use in stalls, due to its large availability and low production costs. Thus, they are usually able to provide a soft lying area for their cows. Nevertheless, the potential positive impact of RMS on cows’ hygiene and odds of hock lesions is not clearly demonstrated. Objectives of this research were to compare RMS-bedded cows’ hygiene level and odds of hock lesions to straw-bedded cows (comparative group). To achieve this, an observational cross-sectional study was conducted in 27 RMS- and 61 straw-bedded herds. During the farm visit, 30 cows per herd were scored for hygiene of three body regions (udder, lower legs and flank/ upper legs) using a score ranging from 1 to 4 (1 being the cleanest and 4 the dirtiest). In addition, both hocks were scored (0 to 3) to evaluate the presence of lesions (0 when there was no lesion and 3 when a swelling protrusion > 2.5 cm was present). Continuation-ratio models were used to compute the odds of having a given score to the odds of having a lower score. RMS usage was associated with lower odds of having an udder hygiene score ≥ 3 (OR: 0.43; 95%CI: 0.20, 0.95) and of having a score of 4 (OR:0.29; 95%CI: 0.09, 0.93). It was also associated, compared to straw, with cleaner lower legs. We observed lower odds of having a score ≥ 2 (OR: 0.45; 95%CI: 0.21, 0.98), ≥ 3 (OR: 0.16; 95%CI: 0.04, 0.66), or a score of 4 (OR: 0.07; 95%CI: 0.01, 0.40) in RMS-bedded herds. No statistically significant association could be highlighted between RMS usage and flank/upper legs hygiene. Furthermore, we did not observe any statistically significant associations between bedding type (RMS vs. straw) and odds of hock lesions. In conclusion, cows bedded with RMS had generally cleaner udders and cleaner lower legs than straw-bedded ones. No association was found between bedding type and odds of hock lesions.